Effects of Authoritarian Leadership on Employees' Safety Behavior: A Moderated Mediation Model - Dawei Wang; Li Wang; Shuangju Wei; Peng Yu; Haichao Sun; Haichao Sun; Ximing Jiang; Yixin Hu (Frontiers Media S.A., 2022)
Safety behavior is one of the focal concerns to occupational health researchers and safety managers. This study examined the relationship between authoritarian leadership and safety behavior based on social exchange theory and locus of control theory, and further explored the mediating role of trust in leadership and the moderating role of locus of control. In this study, a total of 636 employees from petroleum enterprises were recruited, with random sampling used to collect data in two stages. The result showed that: (1) Authoritarian leadership is significantly and negatively related to employees' safety compliance behavior and safety participation behavior. (2) Trust in leadership plays a partially mediating role in the impact of authoritarian leadership on employees' safety compliance behavior and safety participation behavior. (3) Locus of control moderates the first half of the pathway through which authoritarian leadership affects employees' safety behavior through trust in leadership. For externals, the negative effect of authoritarian leadership on their trust in leadership is stronger, which in turn decreases their safety compliance behavior and safety participation behavior.